Aplikasi Metode Regresi Untuk Analisis Variabel Moderasi pada Personel Organisasi Militer - Adi Bandono; Sukmo Hadi Nugroho; Okol Sri Suharyo (Universitas Trunojoyo Madura, 2022)
The achievement of the vision, mission and also the target of a military institution is strongly influenced by soldiers or personnel who are human resource capital. In terms of human resources or personnel, of course, they have work motivation that must be maintained in order to survive in military organizations. Potential human resources and in accordance with their field of work will support the achievement of the organization if they are utilized optimally. This study aims to find answers about how the influence of organizational culture (X1) and job satisfaction (X2) on the work motivation of military personnel (Y) with work facilities as moderating variables (X3). The scientific method used in this research is survey research using a quantitative approach, the data analysis carried out in this study by analysis using statistical model tests. The results obtained in this study are (a) Organizational culture (X1) has a significant effect on work motivation (Y) in Institutions or Military Organizations, (b) Job satisfaction (X2) has a significant effect on work motivation (Y) in Institutions or Organizations. Military, and (c) Work facilities (X3) have a significant effect on work motivation (Y) in Military Institutions or Organizations. Based on the test results, it is also known that there is an effect of these variables after interacting with the work facilities variable as a moderating variable, the results obtained that have a significant effect on the work motivation of personnel. So it can be concluded that work facilities moderate organizational culture and job satisfaction so that it affects the increase in work motivation in military institutions or organizations.